Potential of gamma irradiation on postharvest quality of tomato Solanum lycopersicum L.: a review - M.N.N., Mazumder; A., Misran (Rynnye Lyan Resources, 2022)
Tomato is the most consumed fruit, and an important agricultural product. Losses associated with tomatoes are mainly due to their perishability. Food irradiation using gamma rays is one of the preservation methods which can be used to extend the storage duration while maintaining the sensory quality of tomatoes. This review discussed the potential of gamma irradiation on the postharvest quality aspects of tomatoes through radiation sterilisation. Gamma irradiation has also been proven suitable in delaying the rapid maturity of tomatoes, thus extending their storage life. Doses between 0.5 and 2.5 kGy have been found to maintain the colour, texture, taste, flavour, and overall sensory quality of tomatoes. Gamma irradiation has also been well adopted to control foodborne spoilage and pathogenic microorganisms. Nowadays, many countries allow food irradiation technology as a suitable and cost-effective solution for the problems caused by= various types of insects and microorganisms in fresh produce and food products thereof. This review will thus provide updated and in-depth information useful for the producers, manufacturers, and policymakers alike in the adoption of gamma irradiation for tomato preservation.